Codeine dispensing for privately insured children in the USA: a retrospective database study. Issue 1 (23rd December 2021) - Oliveira J e Silva, Lucas; Anderson, Jana L; Bellolio, Fernanda; Campbell, Ronna L; Jeffery, Molly M
Abstract : In this retrospective study using claims data from the OptumLabs Data Warehouse including 24 658 769 eligible person-years of coverage in the USA, there was substantial decline in codeine dispensing between 2010 and 2019. However, we also observed a persistence of codeine prescribing despite the FDA contraindication in 2018. In 2019, codeine was still being prescribed to children aged 12–17 years at 934 prescriptions per 100 000 person-years of coverage and 106 per 100 000 person-years of coverage in children aged<12 years.